2014
DOI: 10.5296/ijssr.v2i2.5472
|View full text |Cite
|
Sign up to set email alerts
|

A Mosque-Based Economic Empowerment Model for Urban Poor Community

Abstract: Abstra

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In this study, there are at least six steps on mosque-based empowerment, starting from the planning process, socialization, selection, empowering, mentoring, and evalua-tion process. Muslim et al (2014) found the four steps of economic empowerment process for the urban poor community. Firstly, economic empowerment input including mosque-based financial institution, mosque management, beneficiaries, and cooperation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, there are at least six steps on mosque-based empowerment, starting from the planning process, socialization, selection, empowering, mentoring, and evalua-tion process. Muslim et al (2014) found the four steps of economic empowerment process for the urban poor community. Firstly, economic empowerment input including mosque-based financial institution, mosque management, beneficiaries, and cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…Many Islamic economic institutions that exist today, such as zakat, waqf, and also Baitul Maal Wat Tamwil, were born from the mosque. Thus, Muslims should be able to maximize the role of the mosque, especially from the aspect of economic empowerment for the congregation (Muslim et al, 2014). Therefore, mosques must be managed professionally, unlike current business run to gain profit, and then the mosque is managed to provide benefits for the people.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those mosques are Jogokaryan Mosque in Yogyakarta, Nurul Jannah Mosque in Gresik, East Java and Wahidiyah Mosque in Kediri, East Java. They involve actively in empowering Muslim society, stimulate their economic condition and improve their welfare through establishing Shariah cooperatives or Baitul Mal wat Tamwil (BMT) and supporting local small and medium enterprises [5]. Furthermore, Masjid Raya of Pondok Indah sets up a BMT while Masjid Jami' of Bintaro Jaya provides Pinjaman Mikro Masjid (micro loan) to its community [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because, by providing the economic space, the traders are able to increase their earnings who engage in economic activity (Muslim, 2014). MUA Medan as a place of worship cannot be separated from the practice of seeking advantage at the space of worship as a part of an effort to get a benefit in economic practices.…”
mentioning
confidence: 99%